If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6(w-5)-1=-3(-9w+7)-3w
We move all terms to the left:
6(w-5)-1-(-3(-9w+7)-3w)=0
We multiply parentheses
6w-(-3(-9w+7)-3w)-30-1=0
We calculate terms in parentheses: -(-3(-9w+7)-3w), so:We add all the numbers together, and all the variables
-3(-9w+7)-3w
We add all the numbers together, and all the variables
-3w-3(-9w+7)
We multiply parentheses
-3w+27w-21
We add all the numbers together, and all the variables
24w-21
Back to the equation:
-(24w-21)
6w-(24w-21)-31=0
We get rid of parentheses
6w-24w+21-31=0
We add all the numbers together, and all the variables
-18w-10=0
We move all terms containing w to the left, all other terms to the right
-18w=10
w=10/-18
w=-5/9
| 5x+12+3x+24=180 | | 0.4x+2.9=1.52) | | 131+8x+1=180 | | 2a^2-5a=11 | | 45x-90=1935 | | -3=3(x+2)-6x | | 3a+4=2a-5 | | 6(v-90)=4v-34 | | 14x+126=488 | | 150000x10000= | | -0.5t²+10t-32=0 | | 7.5/x+6/x=7.5 | | 7.5/x+6/x=7.51 | | -3.6-(-4.8x+4)=9x+1.1(-8x-6) | | y+5=10 | | 7.5/x+3/x=6 | | 11=x+5.3 | | x-2.7=21 | | 4.8·2=q | | 3)10=4y-6 | | 1/4(8w-4(2))=0 | | (2x–6)(7x+1)= | | 3n+2=n-6 | | (2x–6)(7x+1)=0 | | 3+1=+1=x10 | | 8c×3=96 | | 3x+36=7x-3 | | 3x+36=7x—3 | | Z(z+2)=z²+2z+1 | | 66x=3x | | 66x=3× | | p/9+16=20 |